2018
DOI: 10.1016/j.kint.2017.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Immunoproteasome inhibition prevents chronic antibody-mediated allograft rejection in renal transplantation

Abstract: Chronic antibody-mediated rejection is the major cause of fading allograft function and loss after renal transplantation. Currently, pharmacological agents for the suppression of chronic antibody-mediated rejection are lacking. Non-selective proteasome inhibitors suppress antibody-mediated allograft rejection. However, extensive adverse side effects of these inhibitors severely limit their application. In contrast, immunoproteasome inhibition is effective in preclinical models of autoimmune diseases and was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 39 publications
0
49
0
1
Order By: Relevance
“…Plasma cells that synthesize large amounts of immunoglobulins have a relatively high sensitivity to bortezomib, which partly explains the clinical success of bortezomib in treating plasma cell-derived multiple myelomas. Li et al showed that immunoproteasome inhibition in rats prevented alloantibody production and reduced the number of plasma cells in an antibody-mediated kidney allograft (Li et al 2018). Hence, it seems likely that immunoproteasome inhibition in plasma cells induces ER stress leading to apoptotic plasma cell death and prevention of alloantibody production.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma cells that synthesize large amounts of immunoglobulins have a relatively high sensitivity to bortezomib, which partly explains the clinical success of bortezomib in treating plasma cell-derived multiple myelomas. Li et al showed that immunoproteasome inhibition in rats prevented alloantibody production and reduced the number of plasma cells in an antibody-mediated kidney allograft (Li et al 2018). Hence, it seems likely that immunoproteasome inhibition in plasma cells induces ER stress leading to apoptotic plasma cell death and prevention of alloantibody production.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in an in vitro humoral alloimmunity model, ONX 0914 was shown to decrease alloantibody production (Eleftheriadis et al 2017). In a recent study, the effect of immunoproteasome inhibition has been investigated in a rat kidney transplantation model (Li et al 2018). In this transplantation model, kidneys transplanted from Fischer to allogeneic Lewis rats induce a chronic antibody-mediated allograft rejection.…”
Section: The Immunoproteasome In Kidney Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteasome inhibition is particularly efficient in secretory cells such as plasma cells which has led to the approval of several proteasome inhibitors such as Velcade™, Kyprolis™ , and Ninlaro™ for the treatment of multiple myeloma (see here for examples of clinical trials with proteasome inhibitors). This observation led to the application of proteasome and specific immunoproteasome inhibitors in allograft rejection in humans and several experimental models, however, with mixed results [106][107][108][109][110] . It might be worth considering this therapeutic concept also for B-cell driven autoimmune responses including SSc as suggested previously for autoimmune diseases with renal manifestations 111 .…”
Section: Ups In Autoimmunitymentioning
confidence: 99%
“…The continuous development of surgical techniques and the use of new immunosuppressive agents have significantly improved the short-term survival of renal transplant patients, but the long-term survival rate remains unsatisfactory. A large number of studies showed that antibody-mediated rejection (antibody-mediated renal allograft rejection, ABMR) is one of the most important mechanisms of rejection after renal transplantation (Drachenberg and Papadimitriou 2013;Zhao et al 2017;Li et al 2018). ABMR results in 30-50% of acute rejection episodes and more than 60% of late graft dysfunction.…”
Section: Introductionmentioning
confidence: 99%